(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
Legumes are considered the second most important food source after cereals. One of high protein legume – soybeans is new species for growing in Latvia. Biochemical composition of soybeans is variable dependent on varieties, and highly affected by environmental factors, including fertilisation and the presence of Rhizobium bacteria. Therefore, the present study was conducted to evaluate a chemical composition of soya (Glycine max L) differently fertilized and grown in different places in Latvia. In this study was evaluated protein, fat, fibre content and yield of soybean variety ’Laulema’ grown at different (F1-F6) fertilisation background in Stende and Vilani. Overall results of a three-year analysis (2018-2020) showed that the protein content of soybean ‘Laulema’ ranged from 31.0 to 38.9%, values of total crude fat ranged from 19.4 to 22.4, but crude fibre 10.5-13.7%. Significant difference was observed among fertilisation background, year and climatic conditions. Soybean productivity depends to a large extent on climatic conditions. Providing favourable conditions for the development of Rhizobium bacteria and the availability of balanced nutrients for plants, soybean yield can reach 2 - 3 t ha-2 also in Latvia